Cancer stem cell markers in prostate cancer: an immunohistochemical study of ALDH1, SOX2 and EZH2. Issue 7 (December 2015) - Matsika, Admire; Srinivasan, Bhuvana; Day, Christopher; Mader, Sabrina Ann; Kiernan, Deirdre Margaret; Broomfield, Amy; Fu, Jinlin; Hooper, John D.; Kench, James G.; Samaratunga, Hemamali
Abstract : Summary: The aims of this study were to investigate the immunohistochemical expression and potential prognostic significance of putative cancer stems cell markers ALDH1, EZH2 and SOX2 in prostate cancer. A total of 142 consecutive radical prostatectomies submitted to one laboratory with a diagnosis of prostatic adenocarcinoma between 2008 and 2012 were retrieved and retrospectively studied. Immunohistochemistry for the three markers was performed in each case and both univariate and multivariate analyses were undertaken to evaluate the correlation between the staining patterns and known histopathological prognostic features. ALDH1 showed a statistically significant association with tumour stage p < 0.001), extraprostatic extension ( p < 0.001) and lymphovascular invasion ( p = 0.001). EZH2 correlated with Gleason score ( p = 0.044) and lymph node metastases ( p = 0.023). SOX2 showed a statistically significant correlation with lymphovascular invasion only ( p = 0.018) in both univariate and multivariate analyses. Cancer stem cell markers are variably expressed in prostate adenocarcinoma and immunohistochemical staining for ALDH1 and EZH2 may have a role in predicting tumour aggressiveness before treatment of prostate cancer.